Forensic Engineering 2015 : performance of the built environment : proceedings of the Seventh Congress on Forensic Engineering, November 15-18, 2015, Miami, Florida - Díaz de León, Alicia (ASCE, 2015)
Proceedings of the Seventh Congress on Forensic Engineering, held in Miami, Florida, November 15-18, 2015. Sponsored by the Forensic Engineering Division of ASCE. This collections contains 89 peer-reviewed papers that provide a forum for the development of practices and procedures to advance forensic engineering and provide guidelines for conducting failure investigations and ethical conduct. Topics include: performance of materials; building envelopes; special structures; failures during construction; hurricanes and other natural disasters; and professional practice. This proceedings will be valuable to practitioners and researchers working in all areas of forensic engineering.
Keywords: Forensic engineering -- Congresses.; Structural failures -- Investigation -- Congresses.; elektronické knihy; electronic books